2006
DOI: 10.1159/000090499
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Insulin Resistance and Lipid Peroxidation and Antioxidant Vitamins in Hypercholesterolemic Patients

Abstract: Background: Several studies have reported that insulin resistance and compensatory hyperinsulinemia increased lipid peroxidation, suggesting the linking to each other. We investigated the relationships between insulin resistance index HOMA-IR and lipid peroxidation, plasma antioxidant status in non-diabetic, hypercholesterolemic patients. Methods: We measured the urinary excretion of 8-epi-prostaglandin F2α(PGF2α) levels as a measure of lipid peroxidation in vivo, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Reduced lipid peroxidation may have maintained cell membrane integrity keeping insulin receptor intact, thus may have contributed to increased glucose disposal. The positive relationships seen between TBARS and insulin and TBARS and HOMA-IR in the present study are in agreement with other study findings that increased ROS triggers insulin resistance [49-52]. …”
Section: Discussionsupporting
confidence: 94%
“…Reduced lipid peroxidation may have maintained cell membrane integrity keeping insulin receptor intact, thus may have contributed to increased glucose disposal. The positive relationships seen between TBARS and insulin and TBARS and HOMA-IR in the present study are in agreement with other study findings that increased ROS triggers insulin resistance [49-52]. …”
Section: Discussionsupporting
confidence: 94%
“…This effect seems to be mediated by the activation of peroxisome proliferator‐activated receptor‐γ2 and the subsequent expression of a group of genes related with FA metabolism (21). In addition, in the present study, visceral tissue PUFA were negatively correlated with homeostasis model assessment index, in agreement with Shin et al (22), reinforcing the idea that these FAs also have a protective role against insulin resistance (23).…”
Section: Discussionsupporting
confidence: 93%
“…Shin et al (25) have found an inverse relationship between insulin resistance and plasma total antioxidant capacity, β-carotene and α-tocopherol levels. Dosoo et al (7) have reported that the total antioxidant capacity in Non-IDMM patients reduced in an inverse proportion with fasting blood glucose.…”
Section: Resultsmentioning
confidence: 99%